TRANSPARANSI BIAYA KAMPANYE CALON ANGGOTA DPRD PROVINSI RIAU DAERAH PEMILIHAN KABUPATEN ROKAN HILIR TAHUN 2014 (Studi Kasus : Partai Persatuan Pembangunan) - Sahera, Rio; Tinov, M.Y. Tiyas (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The success of the United Development Party (PPP) in the 2014 election, certainly not apart from one of the main supporters in the general election, namely campaign, election campaign requires every candidate or political party to spend budget. The purpose of this research is to know the transparency of campaign cost of candidate member of Regional Representative Council of Riau Province of Electoral District of Rokan Hilir from United Development Party, and to know the obstacle faced.The type of research used is qualitative research method. The location of this research is conducted on candidate member of Provincial DPRD Riau, DPW PPP Riau Province and related institution Like General Election Commission (KPU) and Election Supervisory Board (BAWASLU) in Election in Riau Province, data collecting technique is done by first in depth interview (in-depth interview) In this interview the researcher uses an interview guide which contains an outline of the subject matter to be questioned, both documentation of this technique is done by using written documents, drawings, photographs or other objects related to the aspects studied. The results of this study indicate that the transparency of campaign costs of candidates for members of the Riau Provincial People's Representative Council. The Electoral District of Rokan Hilir Regency of the United Development Party has not been transparent in the cost factors of boat purchases, elektabilitas survey fees and consultants, open and closed campaign expenses, Voice, shirt fees, t-shirts, campaign jackets, and other campaign attributes, and successful team operational costs and other costs. Obstacles encountered are: a) Reporting of campaign costs is only limited to administrative requirements, b) Prospective members of parliament rarely make reports on campaign costs, c) Lack of socialization of campaign cost reports. Words:Transparency, Campaign Costs, United Development Party.